Utilizing TikTok for Digital Branding in Construction: A Case Study of Havana Sulung - Dimas Setiawan; Ridho Pamungkas; Mei Lenawati; Noordin Asnawi; Galang Romadhona (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study examines the digital branding potential of Mitra Havana Sulung Mandiri, a construction service company in East Java, through the use of TikTok as a promotional platform. The construction industry is traditionally slow in adopting digital media, making this study relevant in exploring new communication strategies. Using observations and interviews, the study identifies the company’s visual strengths—such as project progress updates, before-after visuals, and client testimonials—as effective content for short-form video storytelling. However, internal challenges include limited digital literacy, lack of content production tools, and the absence of standard procedures. External barriers such as skepticism toward social media marketing in the construction field and algorithm changes on TikTok also hinder adoption. Thematic analysis reveals three key needs: utilizing existing visual assets effectively, improving digital skills through internal training, and developing a culture that supports digital transformation. As an initial solution, the study proposes a basic strategy involving educational and behind-the-scenes videos, a simple content production guide, and a 30-day content campaign to test engagement. Collaboration with local creators is also suggested to increase reach. The findings support previous research on the role of short-form video in enhancing brand awareness and trust, particularly in service-based and traditionally conservative industries.